A Bioinspired Orthopedic Biomaterial with Tunable Mechanical Properties Based on Sintered Titanium Fibers. Issue 2 (3rd November 2022) - Rüger, Matthias; Seitz, Andreas Martin; Nuss, Katja; von Rechenberg, Brigitte; Seitz, Daniel; Kostmann, Cris; Quadbeck, Peter; Andersen, Olaf; Collins, Caitlyn
Abstract: Inadequate mechanical compliance of orthopedic implants can result in excessive strain of the bone interface, and ultimately, aseptic loosening. It is hypothesized that a fiber‐based biometal with adjustable anisotropic mechanical properties can reduce interface strain, facilitate continuous remodeling, and improve implant survival under complex loads. The biometal is based on strategically layered sintered titanium fibers. Six different topologies are manufactured. Specimens are tested under compression in three orthogonal axes under 3‐point bending and torsion until failure. Biocompatibility testing involves murine osteoblasts. Osseointegration is investigated by micro‐computed tomography and histomorphometry after implantation in a metaphyseal trepanation model in sheep. The material demonstrates compressive yield strengths of up to 50 MPa and anisotropy correlating closely with fiber layout. Samples with 75% porosity are both stronger and stiffer than those with 85% porosity. The highest bending modulus is found in samples with parallel fiber orientation, while the highest shear modulus is found in cross‐ply layouts. Cell metabolism and morphology indicate uncompromised biocompatibility. Implants demonstrate robust circumferential osseointegration in vivo after 8 weeks. The biometal introduced in this study demonstrates anisotropic mechanical properties similar to bone, and excellent osteoconductivity and feasibility as an orthopedic implant material. Abstract : A novel biometal, based on strategically layered and sintered titanium fibers, mimics the individual anisotropic architecture and mechanical properties of trabecular bone. The resulting open scaffold facilitates the cost‐effective manufacturing of personalized orthopedic implants, promising enhanced interface stability and long‐term survival. The pilot study describes the innovative manufacturing technology, mechanical properties, biocompatibility in vitro, and finally, osseointegration in vivo.